Opto-APC: Engineering of cells that display phytochrome B on their surface for optogenetic studies of cell-cell interactions - Russ, Marissa; Ehret, Anna K.; Hörner, Maximilian; Peschkov, Daniel; Bohnert, Rebecca; Idstein, Vincent; Minguet, Susana; Weber, Wilfried; Lillemeier, Björn F.; Yousefi, O. Sascha; Schamel, Wolfgang W. (Frontiers in Molecular Biosciences, 2023)
The kinetics of a ligand-receptor interaction determine the responses of the receptor-expressing cell. One approach to experimentally and reversibly change this kinetics on demand is optogenetics. We have previously developed a system in which the interaction of a modified receptor with an engineered ligand can be controlled by light. In this system the ligand is a soluble Phytochrome B (PhyB) tetramer and the receptor is fused to a mutated PhyB-interacting factor (PIFS). However, often the natural ligand is not soluble, but expressed as a membrane protein on another cell. This allows ligand-receptor interactions in two dimensions. Here, we developed a strategy to generate cells that display PhyB as a membrane-bound protein by expressing the SpyCatcher fused to a transmembrane domain in HEK-293T cells and covalently coupling purified PhyB-SpyTag to these cells. As proof-of-principle, we use Jurkat T cells that express a GFP-PIFS-T cell receptor and show that these cells can be stimulated by the PhyB-coupled HEK-293T cells in a light dependent manner. Thus, we call the PhyB-coupled cells opto-antigen presenting cells (opto-APCs). Our work expands the toolbox of optogenetic technologies, allowing two-dimensional ligand-receptor interactions to be controlled by light.